A rediscovered fossil hominin fragment from Gombore IB, an early Pleistocene site of Melka Kunture (Upper Awash, Etiopia) - Rubini, Mauro; Gozzi, Alessandro; Altamura, Flavio; Spanò, Ferdinando; Zaio, Paola (Quaternary international, 2025)
The Gombore gully of Melka Kunture is located in the upper Awash Valley of Ethiopia. In the Lower Acheulean layer of Gombore IB, dated to 1.7 million years ago, a well-preserved distal portion of a left humerus was discovered in 1976. Additionally, a proximal fragment of a left humerus was discovered from the same site in 1973; however, it was not initially recognized as belonging to a hominin during excavations. This latter specimen, which was only recently identified within the Gombore I collection, is analyzed here. It is attributed to the middle proximal segment of the bone. The bone presents a significant cortical thickness together with a reduced medullary cavity. Subjected to tomographic examination, it revealed a concentrated cortical structure denoting a young individual. The muscle insertion areas appear well developed and free of apparent musculoskeletal stress. The section appears subcircular with significant diaphyseal torsion that denotes muscular activity. The chronological horizon suggests belonging to Homo erectus. The cross-sectional geometric properties analyses highlight affinity with the first Homo through comparisons with diachronic and synchronic samples. This affinity is probably to be found in the variability of the species and in the bio-complexity at the origin of human evolution.